2016
DOI: 10.1002/2016gl070232
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of submesoscale coastal frontal waves in the East China Sea based on geostationary ocean color imager observational data

Abstract: Oceanic frontal waves are frequently observed, but their life cycles are poorly understood because of the lack of time series data. In this study, the data of geostationary ocean color imager was used to explore the complete evolutionary process of submesoscale frontal waves off the southeast coast of China. Their evolution was analyzed in terms of both wave outline and ridge lines. The process lasted approximately 10 days as the waves propagated southward along the isobaths, accompanied by tidal oscillations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…A similar feature to the modeled cyclone was observed in a section across the western Alborán Gyre (Figure 1b and 1c, near 50 km). Frontal waves and eddies that are qualitatively similar to this modeled feature and the feature on the Alborán Gyre observations have been observed previously, mostly from satellites and photographs from space shuttles, and have been attributed to both shear instability and baroclinic instability (Klymak et al, 2016;Munk et al, 2000;Yin & Huang, 2016). In both cases, the waves are observed to become unstable in 2-3 days and have wavelengths of 20-30 km, consistent with the modeled features.…”
Section: Cut-off Cyclonessupporting
confidence: 86%
“…A similar feature to the modeled cyclone was observed in a section across the western Alborán Gyre (Figure 1b and 1c, near 50 km). Frontal waves and eddies that are qualitatively similar to this modeled feature and the feature on the Alborán Gyre observations have been observed previously, mostly from satellites and photographs from space shuttles, and have been attributed to both shear instability and baroclinic instability (Klymak et al, 2016;Munk et al, 2000;Yin & Huang, 2016). In both cases, the waves are observed to become unstable in 2-3 days and have wavelengths of 20-30 km, consistent with the modeled features.…”
Section: Cut-off Cyclonessupporting
confidence: 86%
“…A similar feature to the modeled cyclone was observed in a section across the western Alborán Gyre (Figure 4-1B,C, near 50 km). Frontal waves and eddies that are qualitatively similar to this modeled feature and the feature on the Alborán Gyre observations have been observed previously, mostly from satellites and photographs from space shuttles, and have been attributed to both shear instability and baroclinic instability (Munk et al, 2000;Yin and Huang, 2016;Klymak et al, 2016). In both cases, the waves are observed to become unstable in 2-3 days and have wavelengths of 20-30 km, consistent with the modeled features.…”
Section: Cut-off Cyclonessupporting
confidence: 85%
“…The spatial resolution is 500 m, and the temporal sampling interval is one hour (eight times per day, from 08:16 to 15:16, UTC+8). Research by Choi et al (2014) and Doxaran et al (2014) showed that GOCI-TSS data can also be applied to near-shore high-turbidity waters, and Yin and Huang (2016) used GOCI-TSS data to describe a complete life cycle of the submesoscale coastal frontal waves in the East China Sea. Therefore, using this data to study the short-term spatiotemporal variation of TSS over the Yangtze Bank is reliable.…”
Section: Hourly Tss Data From the Gocimentioning
confidence: 99%
“…. At the same time, the gradient-based frontal outline method (Yin and Huang, 2016) was applied to extract frontal outlines six times per day (from 09:16 to 14:16). However, the TSS images captured at 08:16 and 15:16 could not extract the frontal outlines due to insufficient spatial coverage ( Figure 2).…”
Section: Hourly Tss Data From the Gocimentioning
confidence: 99%